Impact of ash layer retention on heat transfer in piles of vegetation and structure firebrands. (December 2022) - Wong, Steven; Hodges, Jonathan L.; Lattimer, Brian Y.
Abstract: The study of firebrands has been of great interest due to the growing threat of fires along the wildland-urban interface (WUI). In previous studies, piles of smoldering firebrands from dowels were found to produce higher heat fluxes than those from branches of the same wood species and geometry. In this study, the difference in burning behavior and heat transfer between these two types of smoldering firebrands are explored through experiments and models, using dowels to broadly represent structure fuels and branches for vegetation fuels. A distinct ash layer was observed in the vegetation firebrands that was not present in the structure firebrands. The deposited ash reduces the mass transport of oxygen within the pile which reduces the heat flux to the surface. In piles of ten, structure firebrands produced higher heat fluxes than vegetation firebrands. A 2D RANS model and an analytical burning model were used to demonstrate the impacts of the ash layer on the total burn time, the heat flux, and the surface temperature of a single firebrand by replicating results from the experiments.